THE ROLE of ISLAMIC FINANCE TOOLS in ADDRISSING The BUDGET DEFICIT In MALAYSIA - Ismail , Mahmoud; Karim , Majid (Islamic Sciences Journal, 2023)
Praise be to Allah, Lord of the Worlds, and prayers and peace be upon our master Muhammad and his family and companions After: The purpose of this research, which focuses on the contribution of Islamic financing tools to finance the general budget of the Malaysian state, is to introduce the concept of the budget deficit and its causes, as well as the role played by these tools in financing the general budget of the State. Malaysia markets Islamic capital and Islamic financial architecture, and finally the role of Zakat and Waqf in financing Malaysia's budget deficit In order to achieve the objectives of the study was adopted descriptive analytical method to collect and interpret the information necessary to benefit from the subject of the study.